EDITOR’S NOTES - Sindelar, Melanie Janet (Lidé města, 2024)
This special issue delves into the complexities of decolonization efforts within museums across Central, Eastern, and Southern Europe. These regions, frequently overlooked in global conversations on provenance research and restitution politics, present unique historical and cultural challenges. The focus of this issue is on how museums in these areas engage with their collections – collections shaped by imperialism, internal colonialism, and ideological legacies. Through a series of case studies and theoretical explorations, this issue aims to shed light on how these museums are confronting their pasts and reevaluating their roles in contemporary cultural and political landscapes.